2018
DOI: 10.1111/ajt.14709
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of donor-specific HLA antibodies in living versus deceased donor transplant

Abstract: The presence of donor‐specific anti‐HLA antibodies (DSAs) is associated with increased risk of graft failure after kidney transplant. We hypothesized that DSAs against HLA class I, class II, or both classes indicate a different risk for graft loss between deceased and living donor transplant. In this study, we investigated the impact of pretransplant DSAs, by using single antigen bead assays, on long‐term graft survival in 3237 deceased and 1487 living donor kidney transplants with a negative complement‐depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 36 publications
6
83
1
5
Order By: Relevance
“…A detailed description of the cohort has been published previously. 10 Clinical data were obtained from the Dutch Organ Transplant Registry. Rejection was defined as the presence of biopsy-proved acute rejection (without further classification) or any treatment for acute rejection when no biopsy was performed.…”
Section: Patientsmentioning
confidence: 99%
“…A detailed description of the cohort has been published previously. 10 Clinical data were obtained from the Dutch Organ Transplant Registry. Rejection was defined as the presence of biopsy-proved acute rejection (without further classification) or any treatment for acute rejection when no biopsy was performed.…”
Section: Patientsmentioning
confidence: 99%
“…Many studies using SAB technology revealed pre‐existence or de novo DSA particularly directed at HLA class II to be much more prevalent than was previously found by using less sensitive methods such as CDC or enzyme‐linked immunosorbent assay (ELISA) . Nevertheless, not all patients with DSA as defined by these highly sensitive SAB assays experience ABMR or poor graft survival , questioning the clinical relevance of HLA antibodies only detected in SAB assays. This differential pathogenicity of HLA antibodies could be attributed to differences in IgG subclass composition and complement‐fixing capacity, not detected in standard SAB assays.…”
Section: Why Luminex Sab Data Should Be Interpreted With Cautionmentioning
confidence: 99%
“…In this regard, a positive CDC crossmatch (CDC‐XM) is considered a contraindication for transplantation. While higher sensitivity of flow cytometry crossmatch (FC‐XM) test enables detection of low titer HLA antibodies of all IgG subclasses, DSA detected by solid phase assays alone or in the presence of a positive FC‐XM result were shown to increase the risk of ABMR and graft failure albeit not accounting for high risk in every individual patient . Therefore, the presence of DSA which are not considered a contraindication for transplantation can be used for risk stratification and adaptation of immunosuppressive protocols.…”
Section: Clinical Relevance Of Modified Luminex Sab Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Because our cohort contained a relatively high proportion of living donors and we previously found that DSA had mainly an impact on deceased-donor transplantations with only a limited effect on living-donor transplantations, 19 we also analyzed the impact of non-HLA antibodies on long-term graft survival according to donor status (3276 deceased-donor and 1494 living-donor transplantations). After deceased-donor transplantation, the AKME according to the presence of ARHGDIB antibodies showed a 10-year death-censored graft survival of 61% (95% CI 50%-70%) for the 94 of 3276 patients with and 73% (95% CI 71%-75%) for the 3182/3276 patients without ARHGDIB antibodies ( Table 2).…”
Section: Impact Of Pretransplant Non-hla Antibodies On Long-term Grmentioning
confidence: 99%